Analisis Pengaruh Pengalaman Pengguna, Keamanan Privasi dan Kepuasan Terhadap Repuchase Intention pada Platform E-Commerce - Seniorita; Ibrahim, Mozart Malik; Fadillah, Tri Dessy; Sari, Titis Nistia; Marnilin, Feni; Irawan, Rahmat (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Repurchase intention on e-commerce platforms is the focus of this study, which seeks to assess the impact of user experience, privacy security, and happiness. The majority of people's purchasing decisions in the modern digital age have been made through online marketplaces. Consequently, in order to keep and grow customer loyalty, platform managers must comprehend the elements that impact repurchase intention. This research takes a quantitative approach by surveying 200 who regularly utilize online marketplaces. To examine how the independent variables impacted the dependent variables, the data were subjected to multiple linear regression analysis. The study found that repurchase intention is positively and significantly impacted by user satisfaction, privacy security, and overall user experience. These findings offer valuable insights for e-commerce industry firms looking to enhance their service offerings while prioritizing consumer pleasure, data protection, and positive experiences. In terms of theory, this research adds to what is already known about online shopping habits, particularly as they pertain to Indonesian e-commerce platforms.